The function of PCSK9 in doxorubicin-induced cardiotoxicity and its underlying mechanism - Shuai Shi; Zhihui Qin; Chang Liu; Yanru Zhao; Xiaopeng Bai; Chaoyu Sun; Xu Li; Wanting Cong; Xinyue Yuan; Lixiu Sun; Bingchen Liu; Xueqi Li (Scientific Reports)
Abstract Doxorubicin (DOX) is an anthracycline class of chemotherapy drug, the application of which is limited due to its cardiotoxic effects. Recombinant Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9), is a serine protease pivotal in lipid metabolism and has a profound correlation with the onset of cardiovascular diseases. This study uncovers a connection between PCSK9 and DOX-induced cardiotoxicity (DIC). This research found that injection of DOX in mice caused cardiac toxicity. DOX treatment up-regulated the expression of PCSK9 protein in myocardial tissue. Evolocumab (PCSK9 inhibitors) improved cardiac function, myocardial injury, and fibrosis in DOX-treated mice, indicating a protective effect against DIC. The mechanism involved modulation of cardiomyocyte apoptosis and regulation of apoptosis-related proteins, including Bax/Bcl-2 ratio and Cleaved Caspase-3/Pro Caspase-3 ratio. DOX exhibited concentration- and time-dependent cytotoxic effects on H9C2 cardiomyocytes, promoting apoptosis. PCSK9 nuclear aggregation occurred in H9C2 cardiomyocytes after DOX treatment, and PCSK9 interacted with the Importin subunit beta-1 (KPNB1) protein. Interference with PCSK9 up-regulated KPNB1 expression, affecting apoptosis-related proteins and improving DOX-induced H9C2 cardiomyocyte apoptosis. In short, the elucidation of this mechanism is helpful involve that PCSK9 inhibitor may be a potential drug for improving DIC.